Strategi Pemerintah Kota Malang dalam Meningkatkan Kualitas Pelayanan Publik: Analisis Kritis dan Prospek Perbaikan - Secilya Maharani, Elliza; Fatima, Siti; Pratiwi, Anggini; Hayat (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
The Malang City government's primary goal in addressing the more intricate demands and expectations of the populace is to raise the caliber of public services. This journal article highlights areas that require improvement while critically analyzing the strategies employed by the Malang City government to raise the standard of public services. This was accomplished by performing a thorough examination of the relevant literature on the strategy. The research methodology makes use of a thorough literature analysis from pertinent sources, such as policy papers and associated empirical investigations. The context of the Malang City administration is examined in the study, along with its public service policies, profile, and possibilities and challenges. The plan that the Malang City administration has established is the primary subject of the analysis, which also includes a review of the adopted strategy, a critical analysis of its implementation, and an identification of its shortcomings and obstacles. The examination of success and failure factors, obstacle identification, and strategy implementation evaluation are among the conclusions drawn from the critical implementation analysis. The study offers several suggestions for improvement based on these findings, such as methods for improving implementation effectiveness and estimates of how changes may affect service quality. The interpretation of the analysis's findings, their theoretical links, and their consequences for public service practice and policy are all covered in the findings discussion. Key findings are emphasized in conclusions, which also offer recommendations for further study and application.